PERSEPSI CALON LEGISLATIF PEREMPUAN TERHADAP PEMILU 2004 DAN PERSIAPANNYA MENYAMBUT PEMILU 2009 - Tuti Sulastri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2007)
The Indonesian General Election held in 2004 captured a lot of people ’s attention since the voters could vote directly for their intended candidate for presidency. Another issue that rose was the implementation of the Election Constitution No. 12, 2003, particularly section 65 article I regarding the participation of women in political parties, which at least should be as much as 30%. However, the number of women voted as legislative members was still below 30%. The 2004 Election result shows that out of 30% of female candidates for legislative members, only 11% made their way to the House of Representative. In the House of Representative at the provincial level, the average number is 8% and only 5% at the regent/municipal level. In fact, in a number of Houses of Representative at the regent/municipal level, female legislative members were nonexistent. In Bekasi, the result shows that out of 45 members of the House, 11,1% is female (5 (five) women); three from the Functional Group Party (Golkar), one from the Prosperous Justice Party (PKS), and one from the Indonesian Democratic Party of Struggle (PDI-P). The factors contributing to the above-mentioned failure had something to do with the internal aspects of the female candidates and the implementation of the Election Constitution. Therefore, female legislative members have to make themselves well-prepared before competing in the upcoming General Election of 2009